2016
DOI: 10.1007/s00034-016-0269-8
|View full text |Cite
|
Sign up to set email alerts
|

On Digital Realizations of Non-integer Order Filters

Abstract: Typical approach to non-integer order filtering consists of analogue design and implementation. Digital realization of non-integer order systems is susceptible to problems such as infinite memory requirement and sensitivity to numerical errors. The aim of this paper is to present two efficient methods for digital realization of noninteger order filters: discrete time-domain Oustaloup approximation and Laguerre impulse response approximation. Properties of both methods are investigated with use of non-integer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 42 publications
0
18
0
2
Order By: Relevance
“…The problem of approximating the non-integer order system with an integer order has been analyzed for many years and the most popular approaches are based on Oustaloup transfer function approximation. However, the problem with using the Oustaloup method is that it is very sensitive to high discretization frequencies and rounding errors and can become unstable easily (Baranowski et al, 2016).…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of approximating the non-integer order system with an integer order has been analyzed for many years and the most popular approaches are based on Oustaloup transfer function approximation. However, the problem with using the Oustaloup method is that it is very sensitive to high discretization frequencies and rounding errors and can become unstable easily (Baranowski et al, 2016).…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The implementation of BFF Filtering is not very popular yet, but the authors assume that it will become widely used in the near future due to its efficiency and wider potential in development of frequency filter characteristics. The proposed method also offers more flexible adjustment of frequency characteristics (Baranowski et al, 2016). The previous applied methods have also been presented in studies conducted by Kawala-Janik et al (2014 in more detail.…”
Section: Early-stage Pilot Study On Usingmentioning
confidence: 99%
“…The choice of appropriate filtering is challenging as non-linear filters differ from linear filters, in a way that they could be adaptive. In practice, this means that they retain the so-called edges, which are frequently present in the EEG signals [36][37][38]40,41]. Smoothing filters' (Savitzky-Golay and Median filters) application enables to correct inter alia spikes present in the data [25,27].…”
Section: Applied Smoothing Filteringmentioning
confidence: 99%
“…Our focus was mostly on generalizations of second-order filters developed by Radwan et al [27]. Detailed analysis of method operation was presented in [24].…”
Section: Noninteger Order Filtermentioning
confidence: 99%
“…Most applications of the method can be found in filtering and parametric optimization [21][22][23]. In [24], it was shown that in certain cases and at low orders of approximation LIRA outperforms Oustaloup method.…”
Section: Introductionmentioning
confidence: 99%